Robust H∞ Control of DC Motor in the Presence of Input Delay and Disturbance by the Predictor-Based Method - Nima Maleki; Elahe Moradi (Complexity)
In this study, the speed control of a DC motor with input delay and external disturbance is investigated. A delay-dependent memory state feedback robust predictor-based H∞  controller that formerly has presented is utilized. Sufficient LMIs conditions provide the stabilizing gain of the predictor-based controller. The first-order model of a DC motor has been studied previously using PID and STA (super twisting algorithm) methods. However, in this paper, the delay-dependent robust H∞  controller is used on both the first and second orders of the DC motor. Finally, the predictor-based H∞  controller is compared to the PID controller and the common H∞  controller as well. The simulation results show that the proposed method has been more useful and efficient.